Fully realising the economic potential of women in Australia - Westmore, Ben (OECD Publishing, 2024)
Gender inequalities in Australia have steadily declined, but remain particularly visible in the labour market. Women in Australia have lower employment rates, hourly wages and hours worked than their male counterparts. Childbirth is particularly disruptive for their labour market experience. Reforms to the tax and benefits system, childcare and parental leave arrangements are all needed to reduce the barriers to female labour participation of mothers. At the same time, ensuring the adequacy of unemployment benefits will support the living standards of many low-income women given that they have become an increasing share of recipients. Single mothers face particularly high poverty risk and would also benefit from more robust arrangements around child support payments from non-custodial parents.
OECD Economics Department Working Papers
Keywords: Gender; Income, wealth and finances; International comparison; Labour market